Integration of simulation-based medical education: Student satisfaction and self-confidence at Faculty of Medicine, Jazan University, Saudi Arabia - Abuobaida Yassin (Saudi Journal for Health Sciences)
Background: Simulation-based medical education (SBME) involves using techniques to replicate real scenarios that health profession students will encounter in the clinical areas. Aims: This research aimed to investigate medical student experiences before and after integrating SBME in the internal medicine clerkship courses at the Faculty of Medicine (FOM), Jazan University (JU), Saudi Arabia (SA). Settings and Design: This quasi-experimental design was based on the NLN Jeffries Nursing Education Simulation Framework, which was conducted among medical students at the FOM at JU, SA. Subjects and Methods: Data were gathered through validated questionnaires aligned with the chosen framework: the Educational Practices Questionnaire, the Simulation Design Scale, and the Self-Confidence in Learning Questionnaire. These instruments were translated into Arabic and circulated among 532 medical students enrolled in the internal medicine clerkship courses. Statistical Analysis Used: Data collected from Google Forms underwent analysis using These data had been entered and analyzed using Statistical Package for Social Sciences software version 24.0 (SPSS, Chicago, IL, USA). Frequencies and means were computed for descriptive statistics, and relationships, as well as predictions for student satisfaction and self-confidence, were evaluated through Chi-square tests and multiple regression. Results: A total of 433 students participated, representing an 81.4% response rate. The participants displayed a balanced gender distribution (46.3% being male and 53.7% female). The academic distribution among the participants was diverse, with 38.2% in their 4th year, 34.5% in their 5th year, and 27.3% in their 6th year. A majority of the students (72.9%) exhibited a cumulative grade point average indicative of very good performance. Following the intervention, notable enhancements were observed in simulation design and educational practices. Mean scores for objectives and support experienced a significant increase (P < 0.05). Students’ satisfaction with their learning significantly rose (P = 0.027); however, improvements in self-confidence were not statistically significant. Moreover, the predictors of satisfaction underscored the significance of diverse learning methodologies and clear objectives. The importance of feedback mechanisms for improving satisfaction and self-confidence became apparent, suggesting that customized educational strategies could optimize the advantages of SBME. Conclusions: The current study emphasizes significant enhancements in student contentment and teaching methods after the intervention, emphasizing the value of varied learning approaches. Although the increase in self-confidence was not statistically notable, personalized feedback mechanisms are crucial for improving student experiences in medical education based on simulation. Tailored strategies can optimize educational advantages.